Fat depot‐specific expression of HOXC9 and HOXC10 may contribute to adverse fat distribution and related metabolic traits. (9th December 2015) - Brune, Jakob E.; Kern, Matthias; Kunath, Anne; Flehmig, Gesine; Schön, Michael R.; Lohmann, Tobias; Dressler, Miriam; Dietrich, Arne; Fasshauer, Mathias; Kovacs, Peter; Stumvoll, Michael; Blüher, Matthias; et al.
Abstract : Objective: Independent previous studies in both rodents and humans suggest a role of developmental genes in the origin of obesity and body fat distribution. Here, the hypothesis that human adipose tissue (AT) expression of the developmental genes homeobox transcription factors C9 ( HOXC9 ) and C10 ( HOXC10 ) is fat depot‐specific and related to obesity‐related traits was tested. Methods: In 636 individuals, HOXC9 and HOXC10 mRNA expression was investigated in paired abdominal subcutaneous (SC) and omental AT samples in relation to a wide range of age, BMI, fat distribution, and metabolic parameters and in subfractions of isolated adipocytes and cells of the stromal vascular fraction (SVF). Results: HOXC9 and HOXC10 mRNA expression is significantly higher in SC compared to omental AT. HOXC9 and HOXC10 mRNA expression significantly correlates with body fat mass, even after adjustment for age and gender. In smaller subgroups (depending on the availability of data), fat depot‐related significant gender‐ and BMI‐independent associations between HOXC9 and HOXC10 gene expression and parameters of glucose metabolism and AT biology were found (e.g., adipocyte size). Conclusions: Taken together, these data suggest that HOXC9 and HOXC10 may play an important role in the development of obesity, adverse fat distribution, and subsequent alterations in whole‐body metabolism and AT function.